Debt Heterogeneity and Covenants - Lou, Yun; Otto, Clemens A. (Management Science, 2020)
Coordination failure among owners of heterogeneous debt types increases distress costs. Covenants reduce expected distress costs by lowering the probability of liquidity shortages, increasing liquidation values, and incentivizing creditor monitoring. We predict and find that new debt contracts include more covenants when borrowers’ existing debt structures are more heterogeneous. Our findings suggest that covenants are not only used to address creditor–shareholder conflicts but also to reduce the expected costs of coordination failure among creditors. Furthermore, our results indicate a dynamic component missing from static debt structure models: Debt heterogeneity entails additional covenants (i.e., constraints) when raising future debt. This paper was accepted by Lauren Cohen, finance.